Interdisciplinary Collaboration in Education and Rehabilitation Services for Children with Special Needs: A Phenomenological Study - Tiersa Reinie Undap; Henny Beatryx Adelina Kiriweno (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Children with special needs (ABK) require integrated education and rehabilitation services involving multiple professions. While facilitating interdisciplinary collaboration is necessary to provide holistic and sustainable services, the actual success of interdisciplinary collaboration in the field, is examined through the lens of communication patterns, roles and responsibilities, and larger systems of practice. Objective: The aim of this study was to examine the practices and experiences of professionals with interdisciplinary collaboration in education and rehabilitation services for ABK. Method: This research applies qualitative phenomenological methods. Data were collected through semi-structured in-depth interviews with eight special education teachers, inclusive classroom teachers, occupational therapists, speech therapists, physiotherapists, and psychologists. A purposive sampling technique was used to select the participants. Results: The data analysis generated three primary themes: (1) dynamics of communication in collaboration, which includes formal and informal communication, interprofessional coordination, and the importance of team meetings; (2) role and responsibility negotiation, including authority boundaries, overlapping roles, and management of conflict; and (3) structural and systemic issues, such as resource constraints, administrative burden, and heavy workloads. Conclusion: Interdisciplinary collaboration within ABK education and rehabilitation services can be considered an ongoing process driven by the nature of team interaction, negotiation of professional roles, and the organizational climate. Integrated services for children with special needs are less effective than they could be and could benefit from enhanced communication mechanisms, greater role clarity, and stronger institutional support.